The REST (randomised evaluation of sleeping with a toy or comfort item) trial: a protocol for an online, randomised trial of comfort item use on sleep quality in children - Lepage, Simone; Flight, Laura; Totton, Nikki; Devane, Declan (Contemporary clinical trials communications, 2025)
Randomised controlled trials (RCTs) are the gold standard for evaluating healthcare interventions. Participatory research, in which the public is engaged in research activities, enhances their understanding of trials but requires innovative strategies to reach diverse populations, particularly children. This article outlines the design of the REST (Randomised Evaluation of Sleeping with a Toy or comfort item) trial, a child-led study investigating whether sleeping with a comfort item affects sleep quality in children compared to not using one. The REST trial was created with children aged 7 to 12 through The Kid's Trial, an online initiative where children co-design and co-conduct a randomised trial. The REST trial is a two-arm, pragmatic, superiority RCT. Children worldwide participate from home and are randomly assigned (1:1) to either sleep with or without a comfort item for 7 nights. The primary outcome is sleep-related impairment (SRI), measured using the PROMIS Pediatric Short Form v1.0 Sleep-Related Impairment 4a questionnaire. The secondary outcome is sleep quality, evaluated using a single-item Sleep Quality Scale. Data are collected via online self-reported questionnaires at baseline and eight days post-randomisation. Recruitment is global, targeting caregivers through online media, with study materials available on a dedicated website. The REST trial aims to enrol 292 participants to achieve 80 % power to detect a 3-point difference in SRI. Findings will explore the impact of comfort items on sleep and demonstrate the feasibility and benefits of child-led participatory research, fostering scientific literacy and critical thinking. •This protocol describes the design and rationale of an RCT co-created with children.•The REST trial question and methodology were determined by children aged 7 to 12.•The REST trial was co-designed with kids participating in The Kid's Trial.•The REST trial is a unique example of a global, online, participatory trial with children.